Statistically Defining Optimal Conditions of Coagulation Time of Skim Milk - Celebi, Mithat; Ozdemir, Zafer Omer; Eroglu, Emre; Guney, Ibrahim (CHEM SOC PAKISTAN, 2014)
Milk consist huge amount of largely water and different proteins. Kappa-kazein of these milk proteins can be coagulated by Mucor miehei rennet enzyme, is an aspartic protease which cleavege 105 (phenly alanine)-106 (methionine) peptide bond. It is commonly used clotting milk proteins for cheese production in dairy industry. The aim of this study to measure milk clotting times of skim milk by using Mucor Miehei rennet and determination of optimal conditions of milk clotting time by mathematical modelling. In this research, milk clotting times of skim milk were measured at different pHs (3.0, 4.0, 5.0, 6.0, 7.0, 8.0) and temperatures (20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75 degrees C). It was used statistical approach for defining best pH and temperature for milk clotting time of skim milk. Milk clotting activity was increase at acidic pHs and high temperatures.
Keywords: Milk clotting time; Mucor miehei Rennet; S curve; skim milk; optimization; MUCOR-MIEHEI; CASEIN MICELLES; RENNET; Chemistry